Mouse Infestation Disturbances and Preservation Activities at The Library - Danang Dwijo Kangko; Andrew T. Thren (Institut Agama Islam Negeri Salatiga, 2017)
Information is recorded in information media that is collected by library management. The information will be lost if the collections are damaged. The library functions to preserve collections to ensure information access sustainability. One threat is mouse infestation. Not much attention has been given to the effects of mouse infestation disturbances and how mice can potentially damage collections. This research aims to find out how and why mouse disruptions occur in the library and what preservation measures are taken by the library to counter this. This research is a case study conducted in the Indonesian Politics Study Center. This study reveals that mouse infestation disruptions are not too much of a concern at the Indonesian Politics Study Center, as preservation activities have not been conducted extensively.